Philippine regional profiles 1997 - Pascual, Ruben J.; Belgosa Business Communications (Makati City Belgosa Business Communications, 1997)
Contents: Overview of the Philippines. Features of the specific region. Directories.
Purpose: A series of five yearbooks, each pertaining to the economics, tourism, and business aspects of a region in the Philippines. It also contains directories and yellow pages, as well as detailed descriptions of some areas and issues for each region.
Keywords: Central places -- Philippines -- Guidebooks; Philippines -- Economic conditions -- Directories; Philippine provinces -- Economic conditions